アムンゼン ワン ヤガイ チョウサ タイ ホウコク 1990 (JARE-31) - 小山内, 康人; オサナイ, ヤスト; 高橋, 裕平; タカハシ, ユウヘイ; 田結庄, 良昭; タイノショウ, ヨシアキ; 土屋, 範芳; ツチヤ, ノリヨシ; 蛭田, 真一; ヒルタ, シンイチ; 林, 保; ハヤシ, タモツ; et al. (1991)
P(論文) 第31次南極地域観測隊(JARE-31)夏隊のアムンゼン湾野外調査(10名)は, 1990年2月12日から2月19日までの8日間, アムンゼン湾南部のパドー山およびトナー島で実施され地質, 生物および測地の調査・観測を行った。またこの間夏隊4名によりケーシー湾およびアムンゼン湾沿岸地域において, 「しらせ」S-61ヘリコプターによる偵察・空中写真撮影が行われた。調査地域および偵察・空撮地域はすべて南極地域観測隊にとって初めての調査を行う地域であり, 各種研究・観測上の重要なデータを得た。また, 偵察・空中写真撮影により第32次観測隊以降の調査計画立案のための適地選定も行われた。本報告では, 行動計画およびその実施概要と各部門の成果を簡単に報告する。 The ten-man summer field party of the 31st Japanese Antarctic Research Expedition (JARE-31) carried out geological, biological and geodetic field work at Mt. Pardoe and Tonagh Island in the southernmost part of the Amundsen Bay region. On the other hand, from 12 to 19 February 1990,four men on board S-61 helicopter took aerophotographs of coastal areas around Casey and Amundsen Bays. This report describes the operation planning and summarizes the field operation with a brief report on geological, biological and geodetic field work and the result of aerial photography. departmental bulletin paper